Uniqueness and Existence of Solution for a System of Fractional q-Difference Equations - Wen-Xue Zhou; Hai-zhong Liu (Abstract and Applied Analysis)
We prove the existence and uniqueness of solution for a system of fractional differential equations. Our results are based on the nonlinear alternative of Leray-Schauder type and Banach’s fixed-point theorem.